Catalytic transfer hydrogenation and anticancer activity of arene–ruthenium compounds incorporating bi-dentate precursors - Chang, Yu-Hsiang; Leu, Wohn-Jenn; Datta, Amitabha; Hsiao, Hung-Chang; Lin, Chia-Her; Guh, Jih-Hwa; Huang, Jui-Hsien (Dalton transactions : an international journal of inorganic chemistry, 2015)
Ruthenium based organometallic compounds are presently a subject of great attention as anticancer drugs and appear to work reasonably well on tumor cells. We develop a series of mononuclear arene–ruthenium compounds incorporating N,O and N,N bidentate ligands, and their activity as anticancer drugs against human hormone-refractory metastatic prostate cancer (HRMPCs) cell lines are investigated. The ruthenium compounds also act as effective catalysts in the transfer hydrogenation of the –CO– → –CH(OH)– system. Three types of ligands, namely, sodium glutamate, C 4 H 3 NH(2-CH 2 NH t Bu), and C 4 H 3 NH(2-CHNR) are separately coupled with [(η 6 -cymene)RuCl 2 ] 2 ( 1 ) (cymene = 4-isopropyltoluene) to synthesize five Ru-derivatives: [(η 6 -cymene)RuCl(κ 2 - N , O -OOCCHNH 2 CH 2 CH 2 COOH)] ( 2 ), {(η 6 -cymene)RuCl[C 4 H 3 N(2-CH 2 NH t Bu)]} ( 3 ), {(η 6 -cymene)RuCl[C 4 H 3 N(2-CHNCH 2 Ph)]} ( 4 ), {(η 6 -cymene)RuCl{C 4 H 3 N[2-CHNCH 2 (C 4 H 7 O)]}} ( 5 ) and {(η 6 -cymene)RuCl[C 4 H 3 N(2-CH n BuNHCH 2 (C 4 H 7 O))]} ( 7 ). To the best of our knowledge, the aforementioned Ru compounds are not only characterized by 1 H and 13 C NMR spectroscopy, but for the first time their structures have been established by single crystal X-ray diffractometry. Compound 4 influences a concentration-dependent apoptosis in PC-3 cells and initiates the conversion rate in transfer hydrogenation.